Meningococcal adhesion suppresses proapoptotic gene expression and promotes expression of genes supporting early embryonic and cytoprotective signaling of human endothelial cells - Linhartová, Irena; Basler, Marek; Ichikawa, J; Pelicic, V; Osička, Radim; Lory, S; Nassif, X; Šebo, Peter (FEMS microbiology letters, 2006)
Neisseria meningitidis colonizes the human nasopharynx and occasionally causes lethal or damaging septicemia and meningitis. Here, we examined the adherence-mediated signaling of meningococci to human cells by comparing gene expression profiles of human umbilical vein endothelial cells (HUVEC) infected by adherent wild-type, frpC-deficient mutant, or the nonadherent (DeltapilD) N. meningitidis. Pili-mediated adhesion of meningococci resulted in alterations of expression levels of human genes known to regulate apoptosis, cell proliferation, inflammatory response, adhesion and genes for signaling pathway proteins such as TGF-beta/Smad, Wnt/beta-catenin and Notch/Jagged. This reveals that adhering piliated meningocci manipulate host signaling pathways controlling cell proliferation while establishing a commensal relationship.
Keywords: financování organizované; Oligonucleotide Array Sequence Analysis; apoptóza; zánět; Embryo, Mammalian; průtoková cytometrie; Apoptosis; Up-Regulation; bakteriální proteiny; Bacterial Proteins; lidé; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Flow Cytometry; upregulace; signální transdukce; membránové proteiny; RNA komplementární; stanovení celkové genové exprese; Endothelial Cells; Signal Transduction; Inflammation; Financing, Organized; cytoprotekce; Neisseria meningitidis; Umbilical Veins; endoteliální buňky; Cytoprotection; proteiny fimbrií; Membrane Proteins; venae umbilicales; buněčné kultury; Cell Culture Techniques; RNA, Complementary; bakteriální adheze; embryo savčí; Gene Expression Profiling; Bacterial Adhesion; Fimbriae Proteins; Humans